THE ANALYSIS OF FOOD QUALITY, CITY IMAGE, AND PROMOTION OF REVISITS IN BUKITTINGGI CITY TOURISM WEST SUMATERA WITH CUSTOMER SATISFACTION AS INTERVENING VARIABLE - Safitri, Lucky (Dinasti Publisher, 2022)
The purpose of this study was to examine and analyze the influence of food quality, city image, and promotion on revisit to Bukittinggi City Tourism, West Sumatra with customer satisfaction as an intervening variable. The data used in this study is the result of a questionnaire that was distributed directly in June 2021. Sampling was carried out through a purposive sampling method, in which the researcher had set several criteria. There are 195 respondents in this study. This research method uses PLS-SEM with the help of SMART PLS. The results in this study indicate that food quality has no influence on customer satisfaction, while city image and promotion have a positive and significant influence on customer satisfaction. Meanwhile, food quality and city image have no influence on revisit, while promotion has a positive and significant influence on revisit. Customer satisfaction has a positive and significant influence on revisit. The managerial implications show where innovation needs to be improved which is more attractive and takes advantage of the great potential of Bukittinggi City Tourism, West Sumatra. For further research, it is expected to be able to conduct research in other tourist destinations by using the variables contained in this study to be used as a reference for tourism development in Indonesia